Effects of enoxaparin and unfractionated heparin in prophylactic and therapeutic doses on the fertility of female Wistar rats - Figueiró-Filho,Ernesto Antonio (2014)
PURPOSE: To evaluate the effects of exposure of enoxaparin and unfractionated heparin (UFH) in prophylactic and therapeutic doses on the fertility rates of pregnant healthy Wistar rats.METHODS:Enoxaparin and UFH were administered in prophylactic doses 1 mg/Kg/day 72 UI/Kg/day, and in therapeutic doses at 2 mg/kg/day 400UI/Kg/day. The rats were divided into five groups. The number of live and dead foetuses was quantified. The uterine horns were dissected and the presence of early and late reabsorptions (abortions) was determined. A p<0.05 was considered statistically significant.RESULTS:We did not observe statistically significant differences between groups when comparing the average weight of the foetuses and placentas, rate of female VS males, rates of pre-implantation loss (RPL), rates of efficiency implantation (REI), rates of post-implantation loss (RPIL) and rates of foetal viability (RFV).CONCLUSIONS:There was no significant effect on fertility with the use of anticoagulant drugs in pregnant healthy Wistar rats.